2016
DOI: 10.1186/s13613-016-0176-y
|View full text |Cite
|
Sign up to set email alerts
|

Daily urinary creatinine predicts the weaning of renal replacement therapy in ICU acute kidney injury patients

Abstract: BackgroundIn acute kidney injury (AKI), useless continuation of renal replacement therapy (RRT) may delay renal recovery and impair patient’s outcome. In this study, we aimed to identify predictive parameters that may help to a successful RRT weaning for AKI patients.MethodsWe studied 54 surviving AKI patients in which a weaning of RRT was attempted. On the day of weaning (D0) and the following 2 days (D1 and D2), SAPS II and SOFA scores, 24-h diuresis, 24-h urinary creatinine and urea (UCr and UUr), creatinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 37 publications
2
38
1
1
Order By: Relevance
“…Patients who had to restart dialysis within 14 days were considered unsuccessful, in accordance with previous studies [15,17,18].…”
Section: Data Collection and Definitionsmentioning
confidence: 53%
See 2 more Smart Citations
“…Patients who had to restart dialysis within 14 days were considered unsuccessful, in accordance with previous studies [15,17,18].…”
Section: Data Collection and Definitionsmentioning
confidence: 53%
“…Uchino et al found that a urine output of > 400 ml/day, without diuretics at CRRT cessation, had the greatest AUC value of 0.845, but diuretics negatively affected the predictive ability of urine output [8]. Additionally, a recent study found that the 24 h urine output at the day of attempt of weaning failed to predict successful weaning from RRT [15]. In line with previous studies [8,15,28], our results showed that urine output at the time of CRRT cessation was not significantly associated with successful weaning, and more than 52% of patients in the restarted RRT group received furosemide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other 2 studies did not find a predictive value of urine output for successful RRT discontinuation. Viallet et al [27] reported that 24-h urine creatinine on the first day after RRT weaning but not urine output was the most powerful parameter for predicting RRT weaning success. Frohlich et al [28] also found that 2-h creatinine clearance was a better predictor of remaining CRRT free at day 7 than urine output or serum creatinine.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Recently, daily urinary urea excretion (24 h-urinary urea, 24h-UU) and daily urinary creatinine excretion (24 h-urinary creatinine, 24h-UCr) have been evaluated in 2 different single-center retrospective studies. Both have been demonstrated to be superior than other markers and 24h-UCr than 24h-UU in predicting RRT weaning success [104,105]. …”
Section: Recovery From Aki and Risk To Develop Ckdmentioning
confidence: 99%